Basalt and aramid concentric sheath-core composite fiber and method of making same
Patent Information
- Application Number
- CN202611029909.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-09-29
AI Technical Summary
但玄武岩纤维为刚性无机硅酸盐纤维,表面惰性无活性官能团,无法直接染色;材料脆性大,反复弯折易产生微裂纹、断丝;纤维表面粗糙,织造织物刺肤;与树脂、染料界面结合力极差
在本申请的技术方案中,以无机玄武岩为刚性芯层提供高强度与耐热骨架,以芳纶(间位/对位/杂环)为韧性皮层提高纤维的耐磨与抗冲击性能,并在皮芯界面引入由氨基硅烷和环氧硅烷构成的化学过渡层,利用硅烷偶联过渡液(氨基硅烷和环氧硅烷)的双重反应活性,其中一端能通过化学键(Si-O键)与无机玄武岩牢固结合,另一端(氨基或环氧基)则能与有机芳纶发生反应,其双官能团特性在分子层面将无机-有机界面结合为一体,从而消除传统物理结合易分层的缺陷;该一体化设计通过一步共挤成型实现了高效制备,更使纤维兼具刚韧并济的综合性能,且此设计能够解决两类纤维的固有缺陷,芯层玄武岩提供短时700℃耐火、耐酸碱盐腐蚀、8μm-14μm远红外辐射功能,降低芳纶原料用量,节约生产成本;全覆盖芳纶皮层能够引入酰胺极性基团,使得纤维可直接酸性染料染色,干湿摩擦色牢度提高;芳纶高韧性缓冲弯折应力,弯折疲劳寿命提高,无劈裂断丝现象,织造织物柔软亲肤;复合纤维长期240℃工况稳定使用,突破纯芳纶250℃快速碳化衰减的局限,适配各类中高温柔性应用场景。
Smart Images

Figure CN122833744A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite fiber new material technology, specifically to a basalt and aramid concentric core composite fiber and its preparation method. Background Technology
[0002] Basalt fiber is made from melted and drawn natural basalt. It has a softening point of 960℃, can withstand short-term high temperatures of 700℃, is non-flammable and drip-free, resistant to acid, alkali, and salt corrosion, and can stably release 8μm-14μm far-infrared rays. The raw material cost is low. However, basalt fiber is a rigid inorganic silicate fiber with an inert surface lacking active functional groups, making it unsuitable for direct dyeing. The material is brittle, and repeated bending easily causes micro-cracks and filament breakage. The fiber surface is rough, making woven fabrics irritating to the skin. Furthermore, it has extremely poor interfacial bonding with resins and dyes.
[0003] In existing technologies, basalt high-temperature melt at 1400℃ cannot be co-spun synchronously with aramid dope with a temperature resistance of less than 300℃. The high-temperature melt will carbonize and burn the organic skin layer and the interface modification layer, creating an insurmountable thermal compatibility barrier. Therefore, existing technologies can only achieve composite at the yarn or fabric level, and cannot permanently couple the advantages of the two types of materials at the fiber micro-level. It is difficult to solve the industry pain points of basalt's brittleness and difficulty in dyeing and aramid's insufficient high-temperature resistance at the same time. Summary of the Invention
[0004] In view of the technical problems existing in the background art, this application provides a basalt and aramid concentric core-sheath composite fiber. The basalt and aramid concentric core-sheath composite fiber generates a silane coupling transition layer in situ at the core-sheath interface, and the inorganic phase and organic phase are chemically bonded, so that the core-sheath interface does not separate. By breaking the thermal repulsion barrier between the high temperature inorganic phase and the low temperature organic phase, it has the dual characteristics of high temperature far-infrared function of basalt and flexible and easy processing of aramid.
[0005] To achieve the above objectives, in a first aspect, this application provides a basalt and aramid concentric core-sheath composite fiber, comprising a sheath, a core, and a transition layer; The cortex is located on the outer periphery of the transition layer; the transition layer is located on the outer periphery of the core layer; The core layer volume is 60%-70% of the volume of the basalt and aramid concentric core-shell composite fiber; The cortex volume is 15%-25% of the volume of the basalt and aramid concentric core-shell composite fiber; The skin layer includes at least one of meta-aramid 1313, para-aramid 1414, and heterocyclic aramid; The core layer consists of basalt; The transition layer includes aminosilane and epoxysilane.
[0006] Furthermore, the diameter of the basalt and aramid concentric core composite fiber is 8μm-40μm.
[0007] Secondly, this application also provides a method for preparing basalt and aramid concentric core composite fibers, comprising: We provide basalt ore, aramid fiber raw materials, inorganic high-temperature resistant masterbatch, aminosilane, and epoxysilane. Basalt ore is melted to obtain basalt melt; Aramid dope and inorganic high-temperature resistant masterbatch are mixed to obtain aramid spinning solution; The aminosilane and the epoxysilane are compounded to obtain a silane coupling transition solution; Simultaneous spinning of basalt melt, silane coupling transition liquid and aramid spinning solution yields nascent fibers. The nascent fibers are segmented and simultaneously solidified and fixed, washed, dried and then wound to obtain basalt and aramid concentric core composite fibers.
[0008] Furthermore, the aramid raw material includes at least one of meta-aramid 1313, para-aramid 1414, and heterocyclic aramid; and / or, The solid content of the aramid fiber solution is 18%-23%; and / or, The mass ratio of aramid raw material to inorganic high-temperature resistant masterbatch is (8-9):1.
[0009] Furthermore, the mass ratio of aminosilane to epoxysilane is (1-3):1; and / or, The sum of the mass fractions of aminosilane and epoxysilane in the silane coupling transition solution is 2%-5%.
[0010] Furthermore, the mass ratio of basalt melt, silane coupling transition liquid, and aramid spinning solution is (2-1):(0.2-0.3):1.
[0011] Furthermore, the basalt ore is melted to obtain basalt melt; the melting temperature is 1420℃-1480℃, and the basalt is kept warm at a temperature of 1400℃-1450℃.
[0012] Furthermore, the aramid raw solution and the inorganic high-temperature resistant masterbatch are mixed to obtain the aramid spinning solution; wherein the aramid spinning solution is subjected to heat preservation treatment at a temperature of 40℃-60℃.
[0013] Furthermore, the segmented synchronous solidification and shaping includes a pre-solidification section, a deep solidification section, and a heat-setting tunnel; wherein, the temperature of the pre-solidification section is 20℃-35℃, the temperature of the deep solidification section is 10℃-25℃, and the temperature of the heat-setting tunnel is 80℃-120℃.
[0014] Furthermore, basalt melt, silane coupling transition liquid, and aramid spinning solution are spun simultaneously to obtain nascent fibers; wherein, the extrusion pressure for simultaneous spinning of basalt melt is 0.8MPa-1.2MPa; the extrusion pressure for simultaneous spinning of silane coupling transition liquid is 0.5MPa-0.8MPa; and the extrusion pressure for simultaneous spinning of aramid spinning solution is 0.3MPa-0.5MPa.
[0015] The beneficial effects of this application are as follows: In the technical solution of this application, inorganic basalt is used as a rigid core layer to provide a high-strength and heat-resistant skeleton, and aramid (meta / para / heterocyclic) is used as a tough outer layer to improve the wear resistance and impact resistance of the fiber. A chemical transition layer composed of aminosilane and epoxysilane is introduced at the core-outer layer interface. Utilizing the dual reactivity of the silane coupling transition liquid (aminosilane and epoxysilane), one end can be firmly bonded to the inorganic basalt through chemical bonds (Si-O bonds), while the other end (amino or epoxy group) can react with the organic aramid. Its bifunctional characteristics integrate the inorganic-organic interface at the molecular level, thereby eliminating the defect of easy delamination in traditional physical bonding. This integrated design is achieved through one-step co-extrusion. This design achieves efficient preparation and gives the fiber a combination of rigidity and toughness. It also addresses the inherent defects of both types of fibers. The basalt core provides short-term 700℃ fire resistance, acid, alkali, and salt corrosion resistance, and 8μm-14μm far-infrared radiation, reducing the amount of aramid raw materials used and saving production costs. The fully covered aramid sheath introduces amide polar groups, allowing the fiber to be directly dyed with acidic dyes, improving dry and wet rubbing color fastness. The high toughness of aramid buffers bending stress, increasing bending fatigue life, eliminating splitting and breakage, and resulting in soft, skin-friendly fabrics. The composite fiber can be used stably at 240℃ for extended periods, overcoming the limitation of pure aramid's rapid carbonization and decay at 250℃, making it suitable for various medium- and high-temperature flexible applications.
[0016] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.
[0018] Figure 1 This is a schematic cross-sectional view of the basalt and aramid concentric core composite fiber of this application. Detailed Implementation
[0019] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0021] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0022] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is also expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "a-b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0023] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0024] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0025] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0026] Unless otherwise specified, the terms "comprising" and "including" as used in this application are open-ended. For example, "comprising" and "including" may mean that other components not listed may also be included or contained.
[0027] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0028] The embodiments of this application will be further described in detail below with reference to the accompanying drawings and examples. The detailed description and accompanying drawings of the following embodiments are used to illustrate the principles of this application by way of example, but should not be used to limit the scope of this application, that is, this application is not limited to the described embodiments. Basalt fiber is made by melting and drawing natural basalt, with a softening point of 960℃, short-term high temperature resistance of 700℃, non-flammable and dripping, resistant to acid, alkali and salt corrosion, and can stably release 8μm-14μm far-infrared rays, and the raw material cost is low. However, basalt fiber is a rigid inorganic silicate fiber with inert surface and no active functional groups, so it cannot be directly dyed; the material is brittle, and repeated bending easily produces micro-cracks and fiber breakage; the fiber surface is rough, and the woven fabric is irritating to the skin; the interfacial bonding with resin and dye is extremely poor.
[0029] In existing technologies, basalt high-temperature melt at 1400℃ cannot be co-spun synchronously with aramid dope with a temperature resistance of less than 300℃. The high-temperature melt will carbonize and burn the organic skin layer and the interface modification layer, creating an insurmountable thermal compatibility barrier. Therefore, existing technologies can only achieve composite at the yarn or fabric level, and cannot permanently couple the advantages of the two types of materials at the fiber micro-level. It is difficult to solve the industry pain points of basalt's brittleness and difficulty in dyeing and aramid's insufficient high-temperature resistance at the same time.
[0030] To solve the above-mentioned technical problems, in a first aspect, this application provides a basalt and aramid concentric core-sheath composite fiber, including a sheath layer, a core layer and a transition layer; The cortex is located on the outer periphery of the transition layer; the transition layer is located on the outer periphery of the core layer; The core layer volume is 60%-70% of the volume of the basalt and aramid concentric core-shell composite fiber; The cortex volume is 15%-25% of the volume of the basalt and aramid concentric core-shell composite fiber; The skin layer includes at least one of meta-aramid 1313, para-aramid 1414, and heterocyclic aramid; The core layer consists of basalt; The transition layer includes aminosilane and epoxysilane.
[0031] In the technical solution of this application, inorganic basalt is used as a rigid core layer to provide a high-strength and heat-resistant skeleton, and aramid (meta / para / heterocyclic) is used as a tough outer layer to improve the wear resistance and impact resistance of the fiber. A chemical transition layer composed of aminosilane and epoxysilane is introduced at the core-outer layer interface. Utilizing the dual reactivity of the silane coupling transition liquid (aminosilane and epoxysilane), one end can be firmly bonded to the inorganic basalt through chemical bonds (Si-O bonds), while the other end (amino or epoxy group) can react with the organic aramid. Its bifunctional characteristics integrate the inorganic-organic interface at the molecular level, thereby eliminating the defect of easy delamination in traditional physical bonding. This integrated design is achieved through one-step co-extrusion. This design achieves efficient preparation and gives the fiber a combination of rigidity and toughness. It also addresses the inherent defects of both types of fibers. The basalt core provides short-term 700℃ fire resistance, acid, alkali, and salt corrosion resistance, and 8μm-14μm far-infrared radiation, reducing the amount of aramid raw materials used and saving production costs. The fully covered aramid sheath introduces amide polar groups, allowing the fiber to be directly dyed with acidic dyes, improving dry and wet rubbing color fastness. The high toughness of aramid buffers bending stress, increasing bending fatigue life, eliminating splitting and breakage, and resulting in soft, skin-friendly fabrics. The composite fiber can be used stably at 240℃ for extended periods, overcoming the limitation of pure aramid's rapid carbonization and decay at 250℃, making it suitable for various medium- and high-temperature flexible applications.
[0032] In some embodiments, the diameter of the basalt and aramid concentric core composite fiber is 8μm-40μm.
[0033] In this embodiment, the diameter of the basalt and aramid concentric core-sheath composite fiber is set to 8μm-40μm, which enables the composite fiber to have a certain degree of flexibility and specific surface area, facilitating subsequent textile processing. It also allows the aramid sheath to more uniformly coat the core layer, improving the interfacial bonding effect. Within this range, the composite fiber can leverage the heat resistance of the basalt core layer and provide a certain mechanical strength to the composite fiber, thereby improving its mechanical properties.
[0034] Secondly, this application also provides a method for preparing basalt and aramid concentric core composite fibers, comprising: We provide basalt ore, aramid fiber raw materials, inorganic high-temperature resistant masterbatch, aminosilane, and epoxysilane. Basalt ore is melted to obtain basalt melt; Aramid dope and inorganic high-temperature resistant masterbatch are mixed to obtain aramid spinning solution; The aminosilane and the epoxysilane are compounded to obtain a silane coupling transition solution; Simultaneous spinning of basalt melt, silane coupling transition liquid and aramid spinning solution yields nascent fibers. The nascent fibers are segmented and simultaneously solidified and fixed, washed, dried and then wound to obtain basalt and aramid concentric core composite fibers.
[0035] In this embodiment, basalt ore serves as the inorganic core layer raw material, providing high heat resistance and high strength. The aramid dope solution is mixed with an inorganic high-temperature resistant masterbatch, giving the skin layer toughness and enabling in-situ coloring of the composite fiber. A compound of aminosilane and epoxysilane acts as a coupling agent, providing a foundation for subsequent interfacial chemical bonding. By co-extruding the basalt melt, coupling transition liquid, and aramid spinning solution in a single step within the spinneret assembly, interfacial contamination or reduced bonding strength caused by multi-step processes is reduced, allowing the core layer, transition layer, and skin layer to form a tight concentric structure immediately upon extrusion. By controlling the temperature of the coagulation bath in zones, the skin layer and core layer solidify under suitable conditions, ensuring full solidification and shaping of the aramid in the skin layer and reducing internal stress or microcracks in the basalt core layer caused by rapid cooling. Final washing, drying, and winding improve the cleanliness and winding condition of the composite fiber.
[0036] It can be noted that the solvent used in the aramid raw material can be at least one of N-methylpyrrolidone (NMP), dimethylacetamide (DMAc), and dimethylformamide (DMF).
[0037] It can be noted that the concentric composite spinneret used in this application has an annular high-temperature resistant ceramic heat insulation interlayer and a circulating water cooling structure between the high-temperature melt channel and the low-temperature aramid dope channel. The core melt channel can withstand high temperatures of thousands of degrees, while the skin dope channel maintains a stable process temperature of 4060℃-60℃ through independent water cooling constant temperature control. The conductive and radiative heat of the high-temperature melt is blocked, which structurally reduces the boiling, vaporization, premature curing, or high-temperature carbonization failure of the aramid dope.
[0038] It can be noted that the high-temperature basalt melt and the low-temperature aramid dope in this application are transported through completely independent channels, and only converge and form instantaneously in the millimeter-level area at the outlet of the spinneret micro-orifice, without long-distance high-temperature immersion or thermal contact process. After the melt is extruded from the nozzle, it leaves the high-temperature and high-pressure cavity, and the surface cools down rapidly, quickly forming a low-temperature solidified basalt shell layer, which isolates the internal high-temperature core and prevents the high-temperature melt from directly contacting the organic skin fluid.
[0039] It can be explained that after the nascent fibers of this application exit the nozzle, they immediately enter the low-temperature pre-coagulation zone. Low-temperature air cooling and water mist cause the aramid solution to solidify and solidify first, forming a tightly sealed organic heat-insulating skin. Subsequently, the residual heat inside the basalt core layer is released from the inside out. The heat is buffered, blocked, and dissipated by the already formed aramid skin, reducing the problems of reverse ablation and carbonization of the skin by high-temperature residual heat.
[0040] It can be explained that the silane coupling agent of this application completes the coating and crosslinking at the low-temperature confluence interface at the spinneret exit. The surface layer of the basalt melt is cooled to below 180°C. Under this low-temperature environment, silane molecules stably bond with the basalt silanol groups and aramid groups. After crosslinking, the coupling transition layer is sealed between the core and skin interfaces. The subsequent heat setting temperature is only 80°C-120°C, which is lower than the thermal decomposition temperature of silane, ensuring the long-term stability of the interfacial chemical bonding structure of the composite fiber, with no risk of delamination or failure.
[0041] In some embodiments, the aramid raw material includes at least one of meta-aramid 1313, para-aramid 1414, and heterocyclic aramid.
[0042] In this embodiment, meta-aramid 1313 has good heat resistance and chemical stability, para-aramid 1414 has good mechanical properties and impact resistance, and heterocyclic aramid has good compression resistance. The above three materials can be selected according to the actual situation to improve the performance of composite fibers.
[0043] In some embodiments, the solid content of the aramid solution is 18%-23%.
[0044] In this embodiment, the solid content of the aramid dope is set to 18%-23%, which enables the aramid dope to have a suitable viscosity, so that it flows evenly and is extruded stably during the subsequent spinning process, reducing the occurrence of broken fibers or blockages, achieving a continuous and dense structure of the skin layer, and providing sufficient molecular chain orientation and packing density, thereby improving the mechanical properties and flexibility of the composite fiber.
[0045] In some embodiments, the mass ratio of aramid raw material to inorganic high-temperature resistant masterbatch is (8-9):1.
[0046] In this embodiment, the mass ratio of aramid solution to inorganic high-temperature resistant masterbatch is set to (8-9):1, which can balance the coloring effect and mechanical properties of composite fibers, so that the inorganic high-temperature resistant masterbatch can be evenly dispersed in the spinning solution, providing sufficient color, and maintaining the mechanical properties and modulus of the skin layer itself, thereby achieving coloring of composite fibers while maintaining the mechanical strength and flexibility of composite fibers.
[0047] In some embodiments, the mass ratio of aminosilane to epoxysilane is (1-3):1.
[0048] In this embodiment, the mass ratio of aminosilane to epoxysilane is set to (1-3):1. Aminosilane contains highly reactive amino groups, which can react chemically with amide groups or carboxyl groups in the aramid skin to form chemical bonds. Epoxysilane contains epoxy groups, which have good thermal stability and chemical resistance. Its silanol groups can undergo condensation reactions with the silanol groups on the surface of the basalt core to form Si-O-Si covalent bonds. This mass ratio range allows the silane coupling transition liquid to react fully with the skin and core, thereby improving the bonding strength between the organic and inorganic interfaces of the composite fiber and improving the mechanical properties of the composite fiber.
[0049] In some embodiments, the sum of the mass fractions of aminosilane and epoxysilane in the silane coupling transition solution is 2%-5%.
[0050] In this embodiment, the sum of the mass fractions of aminosilane and epoxysilane in the silane coupling transition liquid is set to 2%-5%, which can form a continuous coupling adsorption layer on the surface of the basalt core layer. This allows the coupling transition liquid to spread and wet the inorganic surface, and undergo a condensation reaction with the silanol groups on the basalt surface. The other end of the coupling molecule in the coupling transition liquid retains enough amino or epoxy groups to chemically bond with the aramid skin layer, constructing a complete molecular bridging network, thereby improving the interfacial bonding strength and mechanical properties of the composite fiber.
[0051] In some embodiments, the mass ratio of basalt melt, silane coupling transition liquid, and aramid spinning solution is (2-1):(0.2-0.3):1.
[0052] In this embodiment, the mass ratio of basalt melt, silane coupling transition liquid, and aramid spinning solution is set to (2-1):(0.2-0.3):1. This provides a suitable proportion of the three components, achieving a structure with uniform skin coating, sufficient chemical bonding in the transition layer, and a reasonable core proportion, thereby improving the interfacial bonding strength, mechanical properties, and flexibility of the composite fiber.
[0053] In some embodiments, basalt ore is melted to obtain basalt melt; wherein the melting temperature is 1420℃-1480℃, and a heat preservation treatment is performed at a temperature of 1400℃-1450℃.
[0054] In this embodiment, the melting temperature is set to 1420℃-1480℃ and a heat preservation treatment is performed. The heat preservation temperature is 1400℃-1450℃, which can match the melting temperature of basalt and allow the basalt to melt fully. Although the heat preservation time is lower than the melting temperature, this temperature range is still higher than the melting temperature of basalt ore. This allows the basalt melt to remain in a molten state before spinning, maintaining the flow dynamics of the melt and facilitating subsequent spinning.
[0055] In some embodiments, aramid dope and inorganic high-temperature resistant masterbatch are mixed to obtain aramid spinning solution; wherein the aramid spinning solution is subjected to heat preservation treatment at a temperature of 40℃-60℃.
[0056] In this embodiment, the aramid spinning solution is heat-preserved at a temperature of 40℃-60℃. This temperature range is lower than the boiling point of the spinning solution and can reduce the viscosity of the spinning solution, so that the aramid spinning solution has sufficient mobility in the subsequent spinning process. In addition, this temperature can maintain the dispersion of inorganic high-temperature resistant masterbatch in the aramid spinning solution, thereby improving the colorfastness and mechanical properties of the composite fiber.
[0057] In some embodiments, the segmented synchronous solidification and shaping includes a pre-solidification section, a deep solidification section, and a heat-setting tunnel; wherein the temperature of the pre-solidification section is 20℃-35℃, the temperature of the deep solidification section is 10℃-25℃, and the temperature of the heat-setting tunnel is 80℃-120℃.
[0058] In this embodiment, the segmented synchronous coagulation and setting includes a pre-coagulation section, a deep coagulation section, and a heat-setting tunnel. The temperature of the pre-coagulation section is 20℃-35℃, the temperature of the deep coagulation section is 10℃-25℃, and the temperature of the heat-setting tunnel is 80℃-120℃. The pre-coagulation section uses a temperature of 20℃-35℃, allowing the nascent fibers just extruded from the spinneret to contact the coagulation medium at a lower coagulation intensity, causing the aramid skin layer to begin initial solidification. Simultaneously, the coupling agent transition layer fully reacts and anchors at the interface. Upon entering the deep coagulation section, the temperature drops to 10℃-25℃. By lowering the coagulation bath temperature, the internal structure of the skin layer is fully coagulated and formed, achieving densification and structural stabilization. This allows the skin layer to obtain sufficient orientation and crystallinity, thereby improving the mechanical strength of the composite fiber. This low-temperature condition can reduce the basalt content in the core layer. Microcracks or internal stress concentrations caused by improper cooling rates during the initial solidification of the rock are addressed by heating the composite fibers in a heat-setting tunnel to 80℃-120℃. This heat treatment removes residual moisture from the composite fibers, reducing performance degradation due to volatilization during subsequent use. Heat setting at temperatures near the glass transition temperature of the aramid layer releases the orientation stress accumulated during solidification, promoting further orderly arrangement of the molecular chains in the layer and improving the dimensional stability and heat resistance of the composite fibers.
[0059] In some embodiments, basalt melt, silane coupling transition liquid, and aramid spinning solution are spun simultaneously to obtain nascent fibers; wherein the extrusion pressure for simultaneous spinning of basalt melt is 0.8 MPa-1.2 MPa; the extrusion pressure for simultaneous spinning of silane coupling transition liquid is 0.5 MPa-0.8 MPa; and the extrusion pressure for simultaneous spinning of aramid spinning solution is 0.3 MPa-0.5 MPa.
[0060] In this embodiment, the extrusion pressure of the silane coupling transition liquid is controlled at 0.5MPa-0.8MPa, which can form a continuous molecular film between the basalt melt core layer and the aramid spinning solution skin layer. The viscosity of the silane coupling transition liquid is much lower than that of the molten basalt and the aramid spinning solution, so a lower pressure can drive it through the microchannel and flow out stably. The extrusion pressure of the basalt melt for synchronous spinning is set at 0.8MPa-1.2MPa to match the spinning process and allow the basalt melt to be extruded normally. The extrusion pressure of the aramid spinning solution for synchronous spinning is set at 0.3MPa-0.5MPa to match the spinning process and allow it to be extruded together with the basalt melt, thereby improving the interfacial bonding strength of the integrally formed composite fiber.
[0061] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0062] I. Preparation Method Example 1 The core layer consists of 70% basalt, the sheath layer of meta-aramid 1313 comprises 25% basalt, and the silane coupling transition layer comprises 5%. The basalt ore is melted and clarified at 1450℃, and the melt is fed into the core layer channel at a holding temperature of 1430℃, with an extrusion pressure of 1.0 MPa. N-methylpyrrolidone and calcium chloride are used as solvents for aramid 1313, the meta-aramid dope solution has a solid content of 20%, and it is conveyed at a holding temperature of 50℃, with an extrusion pressure of 0.4 MPa for the sheath layer. The mass ratio of aminosilane to epoxysilane is 2:1, and a coupling transition liquid with a mass fraction of 3% isopropanol is prepared. The nascent composite yarn is co-extruded using a concentric spinneret in three phases. The yarn is pre-coagulated by air-cooling spray at 25℃, followed by a deep coagulation bath at 15℃ and hot air setting at 100℃. After washing and drying, the yarn has a draw ratio of 1.5 and is wound to obtain the basalt and aramid concentric core-sheath composite fiber with a single filament diameter of 18 μm, as described in Example 1.
[0063] Example 2 The difference from Example 1 is that the core layer basalt accounts for 65% of the volume, the skin layer meta-aramid 1313 accounts for 23% of the volume, and the silane coupling transition layer accounts for 12%. The remaining steps are the same as in Example 1 and will not be repeated here. The basalt and aramid concentric core-skin composite fiber of Example 2 is obtained.
[0064] Example 3 The difference from Example 1 is that the core layer basalt accounts for 60% of the volume, the skin layer meta-aramid 1313 accounts for 25% of the volume, and the silane coupling transition layer accounts for 15%. The remaining steps are the same as in Example 1 and will not be repeated here. The basalt and aramid concentric core-skin composite fiber of Example 3 is obtained.
[0065] Example 4 The difference from Example 1 is that the core layer basalt accounts for 70% of the volume, the skin layer meta-aramid 1313 accounts for 15% of the volume, and the silane coupling transition layer accounts for 15%. The remaining steps are the same as in Example 1 and will not be repeated here. The basalt and aramid concentric core-skin composite fiber of Example 4 is obtained.
[0066] Example 5 The difference from Example 1 is that the core layer basalt accounts for 70% of the volume, the skin layer meta-aramid 1313 accounts for 20% of the volume, and the silane coupling transition layer accounts for 10%. The remaining steps are the same as in Example 1 and will not be repeated here. The basalt and aramid concentric core-skin composite fiber of Example 5 is obtained.
[0067] Example 6 The difference from Example 1 is that the mass ratio of aminosilane to epoxysilane is 1:1. The remaining steps are the same as in Example 1 and will not be repeated here. The basalt and aramid concentric core composite fiber of Example 6 is obtained.
[0068] Example 7 The difference from Example 1 is that the mass ratio of aminosilane to epoxysilane is 3:1. The remaining steps are the same as in Example 1 and will not be repeated here. The basalt and aramid concentric core composite fiber of Example 7 is obtained.
[0069] Example 8 The difference from Example 1 is that the mass ratio of aminosilane to epoxysilane is 0.5:1. The remaining steps are the same as in Example 1 and will not be repeated here. The basalt and aramid concentric core composite fiber of Example 8 is obtained.
[0070] Example 9 The difference from Example 1 is that the mass ratio of aminosilane to epoxysilane is 3.5:1. The remaining steps are the same as in Example 1 and will not be repeated here. The basalt and aramid concentric core composite fiber of Example 9 is obtained.
[0071] Example 10 The difference from Example 1 is that the sum of the mass fractions of aminosilane and epoxysilane in the silane coupling transition liquid is 2%. The remaining steps are the same as in Example 1 and will not be repeated here. The basalt and aramid concentric core composite fiber of Example 10 is obtained.
[0072] Example 11 The difference from Example 1 is that the sum of the mass fractions of aminosilane and epoxysilane in the silane coupling transition liquid is 5%. The remaining steps are the same as in Example 1 and will not be repeated here. The basalt and aramid concentric core composite fiber of Example 11 is obtained.
[0073] Example 12 The difference from Example 1 is that the sum of the mass fractions of aminosilane and epoxysilane in the silane coupling transition liquid is 1%. The remaining steps are the same as in Example 1 and will not be repeated here. The basalt and aramid concentric core composite fiber of Example 12 is obtained.
[0074] Example 13 The difference from Example 1 is that the sum of the mass fractions of aminosilane and epoxysilane in the silane coupling transition liquid is 6%. The remaining steps are the same as in Example 1 and will not be repeated here. The basalt and aramid concentric core composite fiber of Example 13 is obtained.
[0075] Comparative Example 1 Using basalt filaments with a diameter of 20 μm as the core, aramid 1313 short fibers were ring-spun and wrapped around the core, with the total cross-sectional area of the yarn being equivalent to that of the composite fiber monofilament in Example 1, resulting in a core-sheath structure composite fiber of Comparative Example 1.
[0076] Comparative Example 2 Using basalt filaments with a diameter of 20 μm as the core, the surface is impregnated with aramid pulp and dried to form a thin-coated modified fiber, thus obtaining the modified composite fiber of Comparative Example 2.
[0077] Comparative Example 3 The difference from Example 1 is that no silane coupling transition liquid is added for spinning. The remaining steps are the same as in Example 1 and will not be repeated here. The basalt and aramid concentric core composite fiber of Comparative Example 3 is obtained.
[0078] II. Testing Methods Core-shell delamination critical temperature test: Take 100mm long complete basalt core-aramid core fiber samples, with 10 parallel samples per group; suspend the samples horizontally in the constant temperature chamber of a muffle furnace, set the initial temperature to 25℃, the heating rate to 5℃ / min, and hold for 10min after every 20℃ increase; after each holding period, remove a single fiber and observe the fiber cross-section and surface under an optical microscope at 500x magnification, observing whether there are gaps, peeling, flaking, or delamination between the aramid core and the basalt core; if obvious separation gaps or localized peeling of the core and core are observed, record the current holding temperature, which is the critical temperature for core-core delamination of a single sample; after removing the maximum and minimum values, take the arithmetic mean of 8 sets of valid data as the critical temperature for core-core delamination of the finished core fiber; the judgment criteria are that the interface is seamless, without peeling, and without delamination to be qualified; the presence of any separation at the core-core interface indicates that the critical temperature for delamination has been reached.
[0079] Bending fatigue fracture test: Sample pretreatment: The core-sheath fiber was placed in a 23℃, 50%RH environment for 24 hours to achieve humidity equilibration. The effective test length of the sample was 80mm, with 15 parallel samples per group. The curvature radius of the bending clamp head of the testing machine was fixed at 0.5mm, the bending angle was ±90°, and the bending rate was 60 times / min. The two ends of the fiber were fixed to the upper and lower clamps respectively to ensure that the fiber had no pre-tension stress, and the counting device was zeroed. The equipment was started and the bending was continuously repeated, and the number of bending cycles when the fiber completely broke was automatically recorded. After removing the extreme values, the average number of fractures of the effective sample was taken as the bending fatigue fracture count. The constant temperature and humidity environment was maintained throughout the test. If only the sheath of the sample cracked and the basalt core did not break, the bending continued until the core layer completely broke before the data was recorded.
[0080] Far-infrared emissivity test: The core and sheath fibers were combed into uniform and dense fiber mats with a uniform thickness of 0.3 mm, and cut to a size of 100 mm × 100 mm. The test environment temperature was 25℃, the instrument was preheated for 30 minutes, and baseline calibration was performed using a standard blackbody. The fiber sample was flattened and placed on the test sample stage, without wrinkles or gaps. The test band was set to the 4 μm-14 μm room temperature far-infrared band, and the infrared radiation spectrum of the sample was collected. The instrument automatically calculated the average far-infrared emissivity of the sample across the entire band. The same sample was measured 3 times on each side, and the arithmetic mean was taken. Three fiber mats were prepared for each formula and tested separately. The final result was the average of the three sets of samples.
[0081] Acid dyes dry and wet rubbing color fastness test: GB / T 3920-2008 Textiles: Tests for color fastness: Color fastness to rubbing Strength retention rate test: Blank control group: Unaged and uncorroded original core-sheath fibers; the breaking strength of a single filament was tested and recorded as F0, with the average of 10 parallel filaments taken; High-temperature aging group: Fibers were placed in a 300℃ oven for 24 hours and cooled to room temperature before testing the breaking strength F1; Acid corrosion group: Fibers were immersed in a pH=3 dilute sulfuric acid solution at 25℃ for 48 hours, rinsed with pure water, dried, and then tested for breaking strength F2; Strength retention rate calculation formula: High-temperature strength retention rate = (F1 / F0) × 100% Acid corrosion strength retention rate = (F2 / F0) × 100% Interface peeling relative strength test: Complete core-sheath fibers, each 50 mm in length, were cut, with 12 parallel samples per group. A 3 mm length of aramid sheath was locally melted using a micro-thermal knife, and the basalt core fiber end was manually peeled off. Clamps held the exposed basalt core layer and the outer aramid sheath, with an initial spacing of 20 mm between the clamps. The stretching speed was set to 5 mm / min, and a micro-force sensor collected the maximum peeling force F during the peeling process in real time. p Measure the perimeter L of the interface between the fiber sheath and core, and calculate the relative peel strength per unit length: Relative peel strength = Maximum peel force F p / L, in cN / μm; after removing outliers, the average value is taken. The larger the value, the stronger the bond between the basalt core and the aramid skin.
[0082] III. Analysis of Test Results for Each Embodiment and Comparative Example Table 1 shows the test data for Examples 1-13 and Comparative Examples 1-3. Table 2 shows the test data for Examples 1-13 and Comparative Examples 1-3. As shown in Table 1, the critical temperature for delamination in all embodiments significantly exceeds that of the comparative examples. Examples 5 and 13 (coupling layer concentration 10%, total coupling agent mass fraction 6%) reach over 340°C, an 88% increase compared to Comparative Example 1 (180°C) and a 36% increase compared to Comparative Example 3 (250°C) without coupling agent. Example 12 (coupling agent concentration 1%) also reaches a critical temperature of 285°C, still superior to all comparative examples. This demonstrates that the silane coupling transition layer can enhance the interfacial bonding between the basalt core and the aramid skin, thereby improving the thermal stability of the core-skin structure.
[0083] As shown in Table 1, the bending fatigue fracture counts of all embodiments exceeded 9800 cycles, with Examples 1-11 and 13 exceeding 10000 cycles. In contrast, Comparative Example 1 only reached 3100 cycles, Comparative Example 2 only 500 cycles, and Comparative Example 3 only 6200 cycles, showing a significant difference. This indicates that the concentric co-extrusion process enables the aramid sheath to uniformly coat the basalt core, and the coupling transition layer achieves effective stress transfer. This reduces the uneven sheath thickness and stress concentration defects of traditional ring spinning, improving the fiber's bending and fatigue resistance, and meeting the requirements of repeated folding and dynamic service conditions.
[0084] Table 1 shows that the far-infrared emissivity of all samples is above 0.91, with Examples 3, 5, and 13 reaching 0.94, indicating minimal overall difference. Since far-infrared emission performance is primarily determined by the mineral composition of the basalt core layer, the skin layer process and coupling agent formulation have minimal impact. The process described in this application can fully preserve the core advantages of basalt fiber's far-infrared emission. Examples 1-11 and 13 all achieved a dry rubbing color fastness of 4-5 and a wet rubbing color fastness of above 4, while Comparative Example 1 only achieved 2, Comparative Example 2 only 1, and Comparative Example 3 only 3. This indicates that the uniform aramid skin layer provides a stable attachment carrier for acid dyes, and the coupling transition layer reduces skin layer peeling and fuzzing, improving dye adhesion fastness and solving the industry pain point of poor color fastness in traditional modified fibers.
[0085] As shown in Table 2, the strength retention rates of Examples 1-13 after 300℃ heat aging all exceeded 72%, with Examples 5 and 13 reaching over 86%, while Comparative Example 1 only reached 45%, Comparative Example 2 only 38%, and Comparative Example 3 only 65%. This indicates that the concentric co-extrusion molding and coupling transition layer structure can effectively alleviate the thermal stress mismatch between the core layer and the skin layer at high temperatures, reduce the strength attenuation caused by interface peeling, and exhibit better heat resistance than traditional coating and coating modification processes.
[0086] As shown in Table 2, the interfacial peel strength of Examples 1-13 is all above 175% of that of Comparative Example 1, with Example 13 reaching 260%, which is 1.86 times that of Comparative Example 3 without coupling agent. The interfacial strength reaches optimal equilibrium when the mass ratio of aminosilane to epoxysilane is 2:1 (Example 1). This indicates that aminosilane can form chemical bonds with the basalt core layer, and epoxysilane can form an effective bond with the aramid skin layer. All examples showed no thickness variation in the monofilaments, resulting in soft and non-irritating fabrics; however, Comparative Example 1 exhibited large fluctuations in skin thickness and localized roughness, while Comparative Example 2 had uneven coating and a strong irritating feel. This demonstrates that the concentric co-extrusion process can achieve uniform and stable fiber structure, and the coupling transition layer can effectively improve fiber surface roughness and enhance fabric performance.
[0087] In summary, the concentric co-extruded core-sheath structure of "basalt core-aramid skin-silane coupling transition layer" adopted in this application achieves improvements in core dimensions such as interfacial bonding strength, heat resistance delamination performance, bending fatigue resistance, color fastness, and fabric feel compared to traditional ring spinning coating and modification processes. The basalt and aramid core-sheath composite fiber prepared in this application retains the core advantages of basalt fiber, such as high strength, temperature resistance, corrosion resistance, and far-infrared emission, while improving the industry pain points of basalt fiber, such as high brittleness, poor weavability, and difficulty in dyeing, through the aramid skin layer. At the same time, the coupling transition layer achieves a stable bonding between the core and skin interface, which can be widely used in the fields of high-end protective fabrics, aerospace flexible materials, functional textiles, and composite reinforcement materials, and has industrial application value.
[0088] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A basalt and aramid concentric core-sheath composite fiber, characterized in that, Includes the cortex, core, and transition layer; The skin layer is disposed on the outer periphery of the transition layer; the transition layer is disposed on the outer periphery of the core layer; The core layer volume is 60%-70% of the volume of the basalt and aramid concentric core-shell composite fiber; The volume of the outer layer is 15%-25% of the volume of the basalt and aramid concentric core-sheath composite fiber; The skin layer includes at least one of meta-aramid 1313, para-aramid 1414 and heterocyclic aramid; The core layer comprises basalt; The transition layer comprises aminosilane and epoxysilane.
2. The basalt and aramid concentric core composite fiber according to claim 1, characterized in that, The diameter of the basalt and aramid concentric core composite fiber is 8μm-40μm.
3. A method for preparing a basalt and aramid concentric core composite fiber, characterized in that, include: We provide basalt ore, aramid fiber raw materials, inorganic high-temperature resistant masterbatch, aminosilane, and epoxysilane. The basalt ore is melted to obtain basalt melt; The aramid dope and the inorganic high-temperature resistant masterbatch are mixed to obtain the aramid spinning solution; The aminosilane and the epoxysilane are compounded to obtain a silane coupling transition liquid; Simultaneous spinning of the basalt melt, the silane coupling transition liquid, and the aramid spinning solution yields nascent fibers. The nascent fibers are segmented and simultaneously solidified and molded, washed, dried, and then wound to obtain basalt and aramid concentric core composite fibers.
4. The method for preparing basalt and aramid concentric core-sheath composite fibers according to claim 3, characterized in that, The aramid raw material includes at least one of meta-aramid 1313, para-aramid 1414, and heterocyclic aramid; and / or... The solid content of the aramid solution is 18%-23%; and / or, The mass ratio of the aramid raw material to the inorganic high-temperature resistant masterbatch is (8-9):
1.
5. The method for preparing basalt and aramid concentric core composite fibers according to claim 3, characterized in that, The mass ratio of the aminosilane to the epoxysilane is (1-3):1; and / or, The sum of the mass fractions of the aminosilane and the epoxysilane in the silane coupling transition solution is 2%-5%.
6. The method for preparing basalt and aramid concentric core-sheath composite fibers according to claim 3, characterized in that, The mass ratio of the basalt melt, the silane coupling transition liquid, and the aramid spinning solution is (2-1):(0.2-0.3):
1.
7. The method for preparing basalt and aramid concentric core composite fibers according to claim 3, characterized in that, The basalt ore is melted to obtain basalt melt; wherein the melting temperature is 1420℃-1480℃, and heat preservation treatment is performed, wherein the heat preservation temperature is 1400℃-1450℃.
8. The method for preparing basalt and aramid concentric core composite fibers according to claim 3, characterized in that, The aramid raw solution and the inorganic high-temperature resistant masterbatch are mixed to obtain an aramid spinning solution; wherein the aramid spinning solution is subjected to heat preservation treatment at a temperature of 40℃-60℃.
9. The method for preparing basalt and aramid concentric core composite fibers according to claim 3, characterized in that, The segmented synchronous solidification and shaping includes a pre-solidification section, a deep solidification section, and a heat-setting tunnel; wherein the temperature of the pre-solidification section is 20℃-35℃, the temperature of the deep solidification section is 10℃-25℃, and the temperature of the heat-setting tunnel is 80℃-120℃.
10. The method for preparing basalt and aramid concentric core composite fibers according to claim 3, characterized in that, The basalt melt, the silane coupling transition liquid, and the aramid spinning solution are simultaneously spun to obtain nascent fibers; wherein the extrusion pressure for simultaneous spinning of the basalt melt is 0.8 MPa-1.2 MPa; the extrusion pressure for simultaneous spinning of the silane coupling transition liquid is 0.5 MPa-0.8 MPa; and the extrusion pressure for simultaneous spinning of the aramid spinning solution is 0.3 MPa-0.5 MPa.